Theophany verses in the Hebrew psalms - Hunter, J. H. (Old Testament Essays, 1998)
""Theophany"" has been recognised as a literary form in the Hebrew Bible and proliferated as such in many scholarly articles. The theophany appears in all the major Gattungen of the Hebrew psalms. This paper concentrates on theophany verses in the Hebrew psalms with the aim of determining its literary status and its purpose in the various psalms in which it has been used. The interpretations of the theophany are important indicators of the understanding ofYahweh and his role in everyday life in Israel.
free